What Really Matters in Creating Mass Mobilization, Classical Organization or New Social Media? – A Comparative Case Study of the Mass Mobilization Process in France and South Korea - Jeong Im Hyun (Punctum books, 2025)
This article explores why people adopt different processes to participate in mass mobilizations,
using the 2006 Anti-CPE (labor law) Movement in France and the 2008 Candlelight Movement
against American Beef Imports in South Korea as case studies. In France, initiators and
participants followed the ‘ready-made’ way: left-wing organizations led the whole process of mass
mobilizations. In contrast, in South Korea, initiators came from ‘nowhere’: they were middle
and high school students without any political organizations; participants were ‘tainted’ by the
left wing political line. The key finding of this study is that the levels of demarcation of political
lines in people’s everyday life may explain this difference. In France, strong establishment of a
political line in people’s everyday life brought fewer new actors, creating less surprise but a solid
mobilization; in South Koreas, the less-established political line in people’s everyday life attracted
more new actors, creating more surprise but ‘frivolous’ mobilizations.
Jeong-Im Hyun
Center for East Asian Studies, University of Turku
WHAT REALLY MATTERS IN CREATING MASS
MOBILIZATION, CLASSICAL ORGANIZATION OR
NEW SOCIAL MEDIA?
A COMPARATIVE CASE STUDY OF THE MASS
MOBILIZATION PROCESS IN FRANCE AND SOUTH
KOREA
Corresponding author:
Jeong-Im Hyun, Email: hyunjeongim@hotmail.com
Keywords
mobilization process, new media, micro-mobilization, meso-mobilization